(untitled) (Castilla. Estudios de Literatura, 2012)
The literary controversy between tradition and innovation has profoundly affected the post-imperial Spanish literary discourse, when, as a result of the progressive loss of power, the Spanish society began experience a defensive nationalist reaction on the part of her intellectuals. Nationalism and literatue have maintined an intimate relationship in Spain ever since. Pío Baroja, well aware of his marginal status attempts to connect his literatura with the fashionable European impressionist movement, alleging an Spanish origin of the movement because of its mystical components. The result: an original hybridity.